Frost Heaving Damage Mechanism of a Buried Natural Gas Pipeline in a River and Creek Region - Wenxian Su; Shijia Huang (Materials, 2022)
When the buried pipeline passes through the permafrost zone, the phenomenon of frost swelling occurs in the permafrost zone, which causes a certain degree of bending and deformation of the pipeline. As a result, the pipeline’s structural safety is compromised, and the pipeline finally fails during operation, posing a serious hazard to the natural gas pipeline’s operation. Whereas the theoretical research on soil frost heave is relatively comprehensive, the applied research on engineering problems is not yet complete. Therefore, it is necessary to predict frost heaving through experiments and numerical simulation, and put forward reasonable control measures for existing or potential problems. For the problem of pipeline damage caused by frost swelling of soil in the natural gas high-pressure regulator station in a river and creek region, the Drucker–Prager elastic-ideal plastic model of soil was selected for finite element analysis, and a reasonable finite element model of pipe-soil was established in this paper. Through the temperature field analysis, it was found that the soil around the buried pipe is affected by the pipeline and is lower than its freezing temperature, which makes the soil freeze and swell. Furthermore, through the thermal–structural coupling analysis, it was found that the buried pipe is affected by the freezing and swelling of the soil and the structure is greatly likely to be damaged. In addition, by analyzing the temperature distribution and frost heave deformation of the soil around the pipeline, as well as the deformation and force of the pipeline at different pipe temperatures, this paper also determined the ideal temperature for preventing frost heave damage to natural gas at high-pressure regulator stations as −1 °C. Finally, based on the results of the abovementioned analysis, the heating method was determined to improve the frost damage phenomenon at the high-pressure regulator. The results of the anti-frost and swell study were used to conduct field trials at natural gas ...